Anatomical Risk Factors Associated with Immediate Extraction Placement in the Posterior Maxilla: A Human Retrospective Cone-Beam Study - Amato, Francesco; Polara, Giorgio; Prestileo, Chiara (Journal of Dentistry And Oral Implants, 2016)
Purpose: The aim of the study was to analyze the spatial relationship between the sinus floor and the alveolar bone of maxillary premolars and molars in order to assess the amount of basal bone available for immediate extraction placement of endosseous implants. Materials and Methods: All the cone-beam computerized tomographic (CBCT) scans taken over a three-year period at four centers were identified. The subsinus bone height (SBH) was evaluated by measuring the distance between the sinus floor and the first and second premolar root apexes. The interradicular septum bone height (ISBH) of all the first and second molars was also measured, and the presence or absence of sinus-floor invagination between the molar roots was recorded. Results: Five hundred twenty-six (526) CBCT scans of fully or partially dentate maxillary arches were examined. The root apex was inside the sinus of 1.8% of all the first premolars. It approximated the sinus floor of 5.3% of them, and the distance between the two points was between 1 and 3mm of 20%, between 3 and 7mm for 34.1%, and more than 7mm for 34.1%. For the second premolars, the findings were 13.5% (inside the sinus), 10.5% (touching the sinus), 32.8% (1-3mm of distance) 28% (3-7 mm), and 15.2% (more than 7mm). Root invagination was noted in 50.2% of the first molars and 43.1% of the second molars, with the ISBHs ranging from 13.4% to 56.9%. Conclusion: Radiological evaluation is essential to determining whether implants should be placed immediately after extraction of maxillary premolars and molars.
Keywords: subsinus basal bone; immediate placement; maxillary sinus; cone-beam CT; membrane perforation.